Spatial analysis of regency city minimum wage, labor force, regional original income and investment affecting gross regional domestic product in central Java province in 2022 - Darwin Kasidi; Husnul Fitri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Economic growth in Central Java Province is influenced by various regional economic factors, such as the Regency/City Minimum Wage (UMK), labour force, Regional Original Revenue (PAD), and investment, which play an important role in increasing Gross Regional Domestic Product (GRDP). However, economic disparities between regions in the province require in-depth analysis to understand how these factors interact with each other and affect GRDP, as well as to formulate more equitable and sustainable development policies. This study aims to analyze the influence of the variables of Regency/City Minimum Wage (UMK), Total Labor Force (Work), Regional Original Income (PAD), Investment (Foreign Investment and Domestic Capital Investment) on Gross Regional Domestic Product (GRDP) per capita in Central Java Province in 2022 and spatial analysis of these factors in 35 Regency / City in Central Java Province. The analysis is quantitative descriptive using regression analysis techniques and spatial analysis with statistical tests on the GeoDa program. The results show that all four variables, namely MSEs, labour force, PAD, and investment, have a significant influence on GRDP with probability values less than 0.05, indicating that these factors directly contribute to economic growth in Central Java. The pattern of economic concentration found mainly around urban areas, such as Semarang City, suggests an economic spillover effect that drives growth in the surrounding areas. These findings reinforce the important role of investment, PAD management, as well as job creation and MSE adjustment in supporting more equitable and sustainable economic development across the province. This study provides strategic insights for more equitable and sustainable economic development planning in Central Java Province.